Towards nitrogen-rich N-heteropolycycles: synthesis of octaazaperopyrenes (OAPP) - Wesp, Tobias; Bruckhoff, Tim; Petry, Julian; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2022)
Ortho substituted octaazaperopyrenes (OAPPs) are a new class of functional dyes characterized by their strong electron-accepting behavior. Herein, the synthesis, as well as the electrochemical and photo physical properties of an OAPP dye, is reported. The OAPP target was prepared via selective nucleophilic substitution at the peri position of a bay chlorinated tetraazaperylene by introduction of four amino-substituents. The resulting tetraminoperylene was reacted with different acyl chlorides and anhydrides to give the twisted bay chlorinated OAPP derivatives which were isolated in their reduced dihydro-form. The OAPP target could be obtained via a palladium catalyzed dehalogenation and a subsequent oxidation. The eightfold isosteric [CH→N] replacement within the peropyrene core structure results in a large decrease of the frontier orbital energies, rendering the target compound a potent oxidant while preserving the planarity of the aromatic core. The radical anion was obtained by reduction of the OAPP with KC8 and characterized by EPR spectroscopy. A general discussion of the number and location of [CH→N] replacements in peropyrene structures and their frontier orbital energies is provided.
Gesehen am 13.09.2022